Spindle Cell Atypical Fibroxanthoma: Myofibroblastic Differentiation Represents a Diagnostic Pitfall in This Variant of AFX. (July 2015) - Harding-Jackson, Nicholas; Sangueza, Martin; Mackinnon, Alexander; Suster, Saul; Plaza, Jose A.
Abstract : Abstract: Atypical fibroxanthoma (AFX) is a low-grade, dermal, mesenchymal neoplasm, which lacks a specific lineage of differentiation. The classical histologic appearance of AFX is that of a pleomorphic and spindle cell neoplasm with marked nuclear pleomorphism, mitotic figures, and often prominent storiform pattern that superficially resembles a pleomorphic high-grade sarcoma ("malignant fibrous histiocytoma"). Many histologic variants have been described. We have reviewed 15 cases of AFX characterized by a pure spindle cell morphology that could be easily mistaken for other spindle cell dermal neoplasms. All of our cases were stained with CD68, CD163, CD10, S-100p, p63, wide-spectrum keratin, CD31, CD34, smooth muscle actin (SMA), desmin, calponin, and h-caldesmon. All 15 cases showed an immunoprofile consistent with AFX. In 9 cases, SMA was also strongly expressed; this finding, coupled with the malignant spindle cell histomorphology, can lead to an erroneous diagnosis of cutaneous leiomyosarcoma with potential clinical consequences. Awareness of this pattern of immunoreactivity in this unusual variant of AFX is of importance for avoiding diagnostic misinterpretation. This study intends to characterize the nature and frequency of SMA immunoreactivity in AFX and to discuss the potential diagnostic pitfalls of immunohistochemical markers in distinguishing this entity from other malignant spindle cell neoplasms.